Methodological bases and principles of systematics of territorial organization of recreational and tourist activities of the region - Yavorska, V.; Nikolaeva, E. (Journal of Education, Health and Sport, 2017)
The article considers the methodological foundations and principles of the systematics of the territorial organization of the recreational and tourist activities of the region. The role of geographical science in the methodological and methodical development of recreation and tourism is shown. Recreational and tourist activities are analyzed as an intersectoral complex. The role of geographical concepts in the development of this scientific direction, in particular the concept of recreational and tourist resources (destinations) and the concept of territorial recreational systems is defined.